GIST (Generating Interaction Schemata and Text) Strategy on Students’ Reading Ability - Lianora Puspita (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Reading is an extremely complex activity. It is involving combination of linguistics and cognitive abilities. The objective of the research is to know whether GIST (Generating Interaction Schemata and Text) strategy affect students’ reading ability of at second semester of English Study Program of UMB. The research was quasi-experimental design. It was employed the non-equivelent control design. The populations of this study was the second semester English study program students of UMB in academic year 2021/2022. The total number of population was about 32 students. The sample of this research was taken from all of student at the second semester. One class is an experiment class, it used GIST strategy and another without using GIST strategy. The findings of this research showed that there was a significant effect of using GIST strategy on students’ reading ability at second semester English Study Program of University Muhammadiyah Bengkulu. Further research is highly recommended to find as many as good reading strategy and technique to be applied in the classroom. By finding other strategy and technique, it hopes can create better reading ability for the students. Keywords : GIST (Generating Interaction Schemata And Text) Strategy, Reading Ability